EFFICIENCY ASSESSMENT OF AGRICULTURAL LAND USE IN CON CUONG DISTRICT, NGHE AN PROVINCE - Minh Thanh, Nguyen; Thi Bich Phuong, Nguyen; Nhat Hung, Bui (Journal of Forestry Science and Technology, 2018)
Sustainable, economical and effective land use has become an important global strategy. The agricultural land use strategy plays an important role in rural Vietnam as it decides the creation of agricultural and commodity agricultural products as well as the great impact on local people livelihoods. Research results in three communes in Con Cuong district, Nghe An province show that agricultural land use types have been transforming strongly towards sustainable and efficient land use. Research has shown that there are five main Land Use Types (LUTs) in the district. In particular, medicinal plant LUT and orange type V2 bring the highest economic efficiency, environmental and social benefits. Purely agricultural models (rice, maize) do not give highly economical value but play a necessary role in maintaining traditional farming practices and ensuring food security for local people. Research results are a momentous basis for proposing the direction and use of agricultural land with high efficiency and sustainability for the locality.